Visionary Leadership In Islamic Education For Strengthening Religious Moderation And Social Inclusion - Nur Efendi (MUNIF: International Journal of Religion Moderation, 2025)
This study investigates the role of visionary leadership in strengthening religious moderation and social inclusion at Madrasah Aliyah Ummul Akhyar Tulungagung. The study addresses three aspects: leadership vision, implementation of moderation and inclusion, and their impact on students and institutional development. A qualitative descriptive design was applied using in-depth interviews, observations, and document analysis involving school leaders, teachers, and students. Data were analyzed through thematic categorization and interpretive analysis supported by triangulation to ensure credibility. The findings reveal that visionary leadership is articulated through a clear value-oriented vision, exemplary conduct, and strategic alignment of institutional programs. Moderation and inclusion are embedded across curriculum, extracurricular activities, and daily interactions, creating a consistent culture of respect and collaboration. Students demonstrate increased tolerance, openness, and critical awareness in engaging with diversity. Institutional development reflects sustainability through continuous program innovation, stakeholder collaboration, and adaptive practices. The study concludes that visionary leadership provides a coherent and sustainable framework for integrating religious moderation and social inclusion within Islamic education.